HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU DENGAN HASIL TOLAK PELURU GAYA O’BRIEN SISWA PUTRA KELAS VIIb SMP NEGERI 40 PEKANBARU - Jefrianto Jefrianto; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Based on observations conducted by researchers in the field of class VIIb male students of 40 Pekanbaru State Middle School who carried out physical education of bullet material and found problems when making repulsions, there were still many students who were classified as low or categorized as less. The purpose of this study is to prove the presence or absence of a relationship and how much the relationship between arm and shoulder explosive power with o'brien-style bullets of male students of class VIIb SMP Negeri 40 Pekanbaru. This place was conducted at Pekanbaru State Middle School 40, on Garuda Sakti KM.3, Tampan District, Pekanbaru. When the study was conducted in June - December 2018 Based on the results of the research conducted and through the processing of statistical data, it can be concluded that there is a relationship between the strength of the shoulder muscles and the results of o'brient-style bullets. for male students of class VIIb Smp Negeri 40 Pekanbaru because of the low = 0.589 rtable (α = 0.05) = 0.423 It turns out that r count> rtable means Ha is accepted. There is a relationship between variables X and variable Y.Key Words: Arm and shoulder muscle explosive power, bullet firing